Anxiety and Depression in Pediatric Patients with Celiac Disease: A Large Cross-Sectional Study. Issue 2 (1st June 2022) - Germone, Monique; Phu, Tiffany; Slosky, Camryn; Pan, Zhaoxing; Jones, Anna; Stahl, Marisa; Mehta, Pooja; Shull, Mary; Ariefdjohan, Merlin; Liu, Edwin
Abstract : Mental health is a growing concern in pediatric celiac disease (CD). This study utilized the Revised Children's Anxiety and Depression Scale (RCADS) to investigate anxiety and depression symptom rates. Participants were children ages 8 to 17 years (M = 11.7, SD = 2.7; N = 175) with biopsy-proven CD (Median = 1.1 years post-diagnosis, IQR = 0–4) categorized into groups based on the child's age, caregiver or child respondent, presence or absence of comorbidities, and gluten-free diet duration. Self-reported RCADS scores showed 39% of children having clinically significant concerns for anxiety or depression ( P < 0.0001) but only 7% of caregiver-proxy RCADS scores indicated significant concerns for the child's anxiety and 14% for the child's depression. Rates of child-reported anxiety and depression symptoms were significantly higher for those without medical comorbidities than those with ( P = 0.04). Therefore, screening for mental health concerns, particularly anxiety and depression, should be routinely performed in pediatric patients with CD.